Factors contributing to relapse of substance abusers post rehabilitation at the South African National Council on Alcoholism and Drug Dependence, Polokwane, Limpopo, South Africa - Mogoale, Mitjie David (My University, 2021)
PURPOSE OR OBJECTIVE: The purpose of this study was to investigate factors that contribute to the relapse of substance abusers post rehabilitation at South African National Council On Alcoholism And Drug Dependence (SANCA) Polokwane. METHOD: A quantitative research method or approach, and a descriptive research design were employed respectively to conduct the study. Data was collected using group-administered questionnaires / surveys amongst substance abusers who relapsed post rehabilitation at the SANCA, and a total number of sixty-one (61) respondents at the centre responded to the questionnaires. FINDINGS: Findings revealed that personal factors that predisposed the relapse of substance abusers post rehabilitation include lack of coping mechanism; less committed and motivated towards staying clean or sober; having a craving for drugs; challenged with too many triggers; lack of believe in themselves; thinking they could deal with their emotions by using drugs; thinking they could be able to control my use; community members still look down on them for using drugs; peer pressure from peer group; easily influenced by others; significant relationship in their lives ending; social group still abusing drugs; finding it difficult to avoid social gathering; lack of financial support; feeling lonely and being bored. Findings also indicated that substance abuser receive sufficient support from their family. On the contrary, however, findings further show that respondents have indicated that they receive poor from their friends, community members, peers and the rehabilitation centre attended. CONCLUSION: The study successfully identified, and discussed diverse causes or factors that contribute or influence relapse amongst substance abusers post rehabilitation at SANCA, as listed above. Furthermore, also assessing the availability of social support systems post rehabilitation.
Thesis (MPH.) -- University of Limpopo, 2021
Keywords: Factors; Contributing; Substance abusers; Relapse Post Rehabilitation; Social support; Substance abuse; Substance abuse -- Diagnosis; Substance abuse -- Physiological aspects; Diseases -- Relapse; Addicts -- Rehabilitation